Answer:
you multiply the -6 by whats in the parenthesis. so it would be -54, and 54n. Because two negatives make a positive
Hope this helped!
Step-by-step explanation:
Answer:
uumm
Step-by-step explanation:
Answer:
b
Step-by-step explanation:
1.solve for y
2x+4y=12
<u> </u><span><u> -2x -2x</u>
</span><u>4y</u>=<u>12-2x</u>
<u>4 4</u>
y=3-1/2x
step2 plug in y and solve for x
2x+8y=24
2x+8(3-1/2x)= 24
2x+24-4x=24
<u>-2x</u>=<u>0
</u><u>-2 -2</u>
x=0
last step plug in x and solve for y
y=3-1/2x(0)
y=3